Kesamaan Genetik Babi-Manusia: Analisis Biomedis Dan Tinjauan I’jaz Ilmi Dalam Al-Qur’an - Reza Zaki Darmawan Reza (Pascasarjana UIN Raden Mas Said Surakarta, 2025)
This study aims to analyze the genetic similarities between pigs (Sus scrofa) and humans from a biomedical perspective and examine its correlation with the concept of I'jaz Ilmi in the Qur'an. Modern biomedical studies indicate that pigs have a high level of genetic homology with humans, where approximately 80–84% of genetic pathways and functional proteins have structural and functional equivalence. This finding is reinforced by genomic analysis, gene regulation, and epigenetics that show significant biological conservation in metabolic, immunological, and physiological pathways. On the other hand, I'jaz Ilmi provides space to review how the prohibition of pork consumption in the Qur'an contains scientific wisdom relevant to potential biomedical risks, such as zoonosis, mixing vessel properties, and cellular compatibility that allows the transfer of pathogens between species. Through an integrative approach, this study concludes that the genetic closeness of pigs and humans not only provides important value for medical research, but also confirms the scientific wisdom aspect in the prohibition of pork consumption as stated in the Qur'anic text. This study is expected to enrich interdisciplinary insights between modern medical science and Qur'anic scientific studies.